Actuator failure compensation for two linked 2WD mobile robots based on multiple-model control - Ma, Yajie; Cocquempot, Vincent; El Badaoui El Najjar, Maan; Jiang, Bin (Zielona Góra: Uniwersytet Zielonogórski)
This paper develops a new actuator failure compensation scheme for two linked two-wheel drive (2WD) mobile robots based on multiple-model control. First, a configuration of two linked 2WD robots is described, and their kinematics and dynamics are modeled. Then, a multiple-model based failure compensation scheme is developed to compensate for actuator failures, consisting of a kinematic controller, multiple dynamic controllers and a control switching mechanism, which ensures system stability and asymptotic tracking properties. Finally, simulation results verify the effectiveness of the proposed failure compensation control system.
Keywords: actuator failure; multiple-model control; physically linked robots; two-wheel drive